Sebuah Model Prediktif Pengembangan Aglomerasi Perkotaan di Provinsi Kalimantan Timur dengan Metode Analisis Klaster - Novedy, Anita Claudia; Sasongko, Ibnu; Santosa, Endratno Budi; Afrianto, Firman (Program Studi Teknik Informatika Universitas Pamulang, 2025)
The development of the new capital in East Kalimantan Province is guided by agglomeration as a strategic framework, aiming to reduce regional disparities and maintain a balance between the central area and its surrounding regions. This strategy is reinforced by the development of the transportation sector, which provides the foundation for both geographic and administrative connectivity across regions. The concentration of activities, including industry, trade, government, and infrastructure, is a key driver of economic growth and regional development. This study employs a quantitative approach supported by Geographic Information Systems (GIS), specifically the DBSCAN algorithm, using a road network shapefile (.shp) as the primary data. The results of the analysis show that Bontang, Balikpapan, and Samarinda City function as the trigger nodes driving regional activity concentration and growth, with development trends expanding towards the north and west. Predictive analysis using DBSCAN at distances of 1,600–2,400 meters indicates that 9 out of 10 regions in East Kalimantan Province have formed new growth centers, except that Mahakam Ulu Regency has not yet shown signs of urban agglomeration.